Comparison of Stress Coping Strategies of Socially Vulnerable Young People in Lithuania and Latvia - Vaitkevičienė, Asta; Alifanovienė, Daiva; Kepalaitė, Albina; Šapelytė, Odeta; Gerulaitis, Darius (Socialinė teorija, empirija, politika ir praktika, 2024)
The article addresses the issue of stress coping of socially vulnerable young people. Coping methods and strategies are analysed regarding the socio-cultural context. A quantitative study was conducted to reveal the coping methods and strategies of socially vulnerable young people aged 18–29 from Northern Lithuania and Southern Latvia. Vulnerable young people in the two Baltic States use different coping strategies and sets of coping strategies which may be related with socio-cultural reasons, different content of the social service package, availability and content of psychological and social support.
Keywords: coping with stress; coping strategies; socially vulnerable young people; intercultural context; social support